Decolonising international law : development, economic growth, an d the politics of universality - Pahuja, Sundhya (New Delhi: Cambridge University Press, 2012)
"The universal promise of contemporary international law has long in spired countries of the Global South to use it as an important field of contestation over global inequality. Taking three central examples, Su ndhya Pahuja argues that this promise has been subsumed within a univer sal claim for a particular way of life by the idea of 'development'. As the horizon of the promised transformation and concomitant equality ha s receded ever further, international law has legitimised an ever-incre asing sphere of intervention in the Third World. The post-war wave of d ecolonisation ended in the creation of the developmental nation-state, the claim to permanent sovereignty over natural resources in the 1950s and 1960s was transformed into the protection of foreign investors, and the promotion of the rule of international law in the early 1990s has brought about the rise of the rule of law as a development strategy in the present day"--
Introduction -- Inaugurating a new rationality -- From decolonisatio n to developmental nation state -- From permanent sovereignty to invest or protection -- Development and the rule of (international} law -- Co nclusion.
Includes bibliographical references (p. 270-293) and index.
Keywords: International law; Postcolonialism; Law and economic development